Análise da variabilidade pluviométrica da região da UHE – Tucuruí/PA no período operacional (1988-2017) - ALMEIDA, Denilson Freitas (Universidade Federal do Pará, 2020)
The Tocantins - Araguaia hydrographic region has become a major power in the generation of hydraulic energy with the installation of large hydroelectric plants and the formation of several artificial lakes, resulting in hydrological changes and possible changes in the microclimate and rainfall. The analysis of rainfall behavior in the hydrographic basin becomes of fundamental importance for the management of water resources. In order to subsidize the management and planning of water resources in the region, an analysis of the spatial-temporal rainfall variability was carried out in the Lake HPP-Tucuruí / PA region, being divided into 4 quadrants (NE, NO , SO and SE) and 12 sub-areas (NE50, NE100, NE200, NO50, NO100, NO200, SO50, SO100, SO200, SE50, SE100 and SE200), considering the period of 30 years (1988-2017), in order to analyze the behavior of the rains in the region. To this end, data were collected and analyzed from 30 pluviometric stations that appear in the database of the ANA platform (HidroWeb base), within a radius of up to 200 km from the hydroelectric plant. With the aid of the QGIS 3.0.3 software, the isohyets maps were drawn using the linear ordinary kriging interpolation method, representing the heights of the water slides. The results showed variability in the spatial and temporal distribution of the total volume precipitated in the referred period of study, identified in the results of standard deviation and variance, in addition to the result of the trend of rains by Mann Kendall's non-parametric tests. The pluviometric indexes showed decreases, when analyzing the entire study area, with an average rainfall of 2157.73 mm. There was a greater decrease in precipitation in the southern part of the region, which showed lower rainfall. In the northern regions, where the artificial lake formed by the Tucuruí dam is found, there were higher rainfall averages. The Mann-Kendall (MK) results showed a greater decrease in the quadrants of the microscale (close to the bus), especially at NO50, which showed a significant trend of decreasing rainfall in the study region (Z = -2.24).